Production and Optimisation of Parameters for Density and Ash Content of Briquettes Produced from Sorghum Stalks and Groundnut Shells Using African Locust Bean (Parkia biglobosa) Pulp as a Binding Agent - Abdulkarim AMINU; Mohammed ALIYU; Ibrahim S. MOHAMMED; Iyanda M. ANIMASHAUN; Peter DANIEL; Mohammad USMAN (FUDMA Journal of Engineering and Technology, 2025)
To address the climatic challenges posed by conventional fossil fuels, prioritizing research on renewable energy sources is essential. This study aims to develop briquettes from a blend of carbonized sorghum stalks and groundnut shells to mitigate environmental issues associated with the use of fossil fuels. The biomass materials were subjected to carbonization at 400°C for 1 hour within a muffle furnace. The production process utilized a D-Optimal Design of Experiment to optimise independent variables, including the ratios of sorghum stalks and groundnut shells, compaction pressure, and particle size, with briquette density and ash content as response parameters. The results revealed a biochar yield of 37.25% for sorghum stalks and 57.50% for groundnut shells. Briquette densities ranged from 0.64 to 1.36 g/cm³, and ash content varied from 7.55% to 18.55%. Statistical analysis revealed that increased compaction pressure and reduced particle size resulted in higher briquette density, whereas the ratios of biomass materials had a minimal effect on this outcome. The optimal briquette formulation was determined to be 30 wt.% sorghum stalks and 30 wt.% groundnut shells, with a compaction pressure of 12 MPa and a particle size of 0.78 mm. This formulation yielded a density of 1.2 g/cm³ and an ash content of 8.710%, resulting in a maximum desirability index of 0.944. The successful creation of these briquettes suggests a viable renewable energy source that could help reduce reliance on conventional fossil fuels and address climate change. This development supports renewable energy production and sets the stage for further research and policy efforts in biomass energy technology.